P-P38 External validation of post-operative pancreatic fistula prediction scores in pancreatoduodenectomy: a systematic review and meta-analysis. (16th December 2021) - Pande, Rupaly; Halle-Smith, James; Phelan, Liam; Thorne, Tom; Hodson, James; Roberts, Keith J; ,
Abstract: Background: Multiple risk scores claim to predict the probability of post-operative pancreatic fistula (POPF) after pancreatoduodenectomy. It is unclear which scores have undergone external validation which score is the most accurate. Objective: To identify risk scores and assess the clinical validity of these scores. Methods: Areas under receiving operator characteristic curve (AUROCs) were extracted from studies that performed external validation of POPF risk scores. These were pooled for each risk score, using intercept-only random-effects meta-regression models. Results: Systematic review identified 34 risk scores, of which six had been subjected to external validation, and so were included in the meta-analysis, namely the Tokyo (N = 2 validation studies), Birmingham (N = 5), FRS (N = 19), a-FRS (N = 12), m-FRS (N = 3) and ua-FRS (N = 3) scores. The overall predictive accuracies were found to be similar for all six scores, with pooled AUROCs of 0.61, 0.70, 0.71, 0.70, 0.70 and 0.72, respectively. Considerably heterogeneity was observed, with I2 statistics ranging from 52.1-88.6%. Conclusions: Most risk scores lack external validation, their predictive accuracies were limited and similar across risk scores. Consensus is needed for which score to use in clinical practice. Due to the limited predictive accuracy, future studies to derive a more accurate risk score are warranted.